The Impact of Green Banking on Profitability of Indonesia’s Islamic Commercial Banks - Khoirul Umam; Alfi Khilmi Khusnia; Vina Fithriana Wibisono; Naahilah Hunafaa' Al-Qudsy (Universitas Muhammadiyah Sidoarjo, 2025)
The intensifying competition within the banking industry has driven institutions to adopt strategies that not only focus on profitability but also uphold sustainability values. Among these initiatives, green banking; representing a form of green investment within the Islamic financial framework; has become a key approach. This study investigates how green banking practices, and the number of ATMs affect the profitability of Islamic commercial banks in Indonesia, using Return on Assets (ROA) as the performance measure for the 2019–2024 period. Using a quantitative approach, the research applies panel data regression with a Fixed Effect Model (FEM). The results reveal that green banking practices do not have a significant impact on bank profitability. Although theory suggests a positive correlation, the empirical results reveal that its contribution to improving ROA remains unproven, likely due to its limited and long-term implementation stage. Similarly, the number of ATM units shows no significant effect and even tends to negatively affect profitability, possibly because of high operational expenses and customers’ growing shift toward digital banking services. Despite the insignificant short-term impact, the incorporation of environmentally friendly banking measures by Islamic banks represents an essential step toward incorporating environmentally responsible financing and energy efficiency. This approach holds promising potential to enhance the sustainability, reputation, and competitiveness of Islamic banks in the long term.